Preparation and Characterization of Reduced Graphene Oxide Sheets via Water-Based Exfoliation and Reduction Methods - Vorrada Loryuenyong; Krit Totepvimarn; Passakorn Eimburanapravat; Wanchai Boonchompoo; Achanai Buasri (Advances in Materials Science and Engineering)
This research studied the synthesis of graphene oxide and graphene via a low-cost manufacturing method. The process started with the chemical oxidation of commercial graphite powder into graphite oxide by modified Hummer’s method, followed by the exfoliation of graphite oxide in distilled water using the ultrasound frequency from a laboratory ultrasonic bath. Finally, the oxygen functional groups on exfoliated graphite oxide or graphene oxide were eliminated by stirring in hot distilled water at 95°C, as a replacement for highly toxic and dangerously unstable hydrazine. The results assured that stirring in hot distilled water could give the product of graphene or reduced graphene oxide. The samples were characterized by FTIR, XRD, TGA, Raman spectroscopy, SEM, and TEM methods.